Anti‐Inflammatory Effects of Opuntia Milpa Alta Polysaccharides Fermented by Lactic Acid Bacteria in Human Keratinocyte HaCaT Cells. Issue 5 (26th April 2022) - Zhang, Yuzhi; Liu, Pingping; You, Shiquan; Zhao, Dan; An, Quan; Wang, Dongdong; Zhang, Jiachan; Li, Meng; Wang, Changtao
Abstract: Opuntia milpa alta polysaccharides (ODP) are bioactive compounds extracted from Opuntia milpa alta and widely used in the treatment of diseases, but the therapeutic mechanism of ODP on inflammatory injury remains unclear. Therefore, this study explores the effects and mechanisms of ODP in lipopolysaccharide (LPS)‐induced inflammation of human keratinocytes (HaCaT). In this experiment, ODP was extracted via the water extraction and fermentation methods, respectively. LPS was then used to induce inflammatory damage in HaCaT cells, and the stimulated cells were treated with different concentrations of ODP. Cell viability was detected by MTT assay, and the concentrations of COX‐2, iNOS, IL‐6, IL‐8, IL‐10 and TNF‐α were determined by enzyme‐linked immunosorbent assay (ELISA). Changes in inflammatory cytokines and related mRNA expression were observed to assess LPS‐induced cell damage. In the experiment, it was found that the LPS stimulation of HaCaT cells can induce cellular inflammatory response, reduce cell viability, increase cell apoptosis and increase the expression of COX‐2, iNOS, IL‐6, IL‐8, IL‐10 and TNF‐α. However, the experimental data shows that ODP can reverse the above results by increasing cell viability, inhibiting cell apoptosis, reducing the expression of the above genes and inactivating antioxidant pathways, which revealed the specific mechanism of ODP repairing LPS‐induced inflammatory damage to Hacat cell. In addition, The experimental results showed that fermentation could improve the anti‐inflammatory effect of ODP. In conclusion, our experimental results indicate that ODP fermented by lactic acid bacteria can be used as an anti‐inflammatory agent. Abstract :